Increasing Production of Potato (Solanum tuberosum L.) Var. Nadia at Medium Land Through Application of Compost Goat Manure and Potassium - Nunun Barunawati; Nur Fahmi Zakariyah (PLANTROPICA: Journal of Agricultural Science, 2016)
Potato production in the highlands is decreasing, therefore it is necessary to increase the yield. This research aims to obtain the interaction between doses of KCl and compost on the growth and yield of potato variety Nadia. The Nadia variety is one of the potato which is tolerate to high temperature and medium land. The research conducted on February until May 2016 in Klino, Bojonegoro, 750 m asl. The research method was using randomized block design that consist with two factors; organic and inorganic fertilization. There are two levels of compost fertilization: 10 ton ha-1 (K1), 20 ton ha-1 (K2) and KCl fertilizer consist of four levels; 100 kg KCl ha-1 (P0), 150 kg KCl ha-1 (P1), 200 kg KCl ha-1 (P2), 250 kg KCl ha-1 (P4). There were eight combinations with four replication. The results showed that there were interaction between the dose of KCl and compost on the parameters: number of leaves, number of stems, height of plant, leaf area, total content of chlorophyll, total number of tubers per plant, weight of tuber per plant, weight tuber per plot, and total harvest. The results showed combination of doses compost 20 ton ha-1 and dosage of KCl 150 kg ha-1 had the optimum result of total yield potato.